Wooden or metal: live-trap type preferences of small mammals in relation to habitat, taxon, and sex - Łukasz Jankowiak; Anke Hoffmann; Jan Decher; Michał Szkudlarek; Nicola Eccel; Patrycja Popiel; Bogna Malinowska; Oliwia Sęk; Leszek Rychlik (Mammalian Biology, 2026)
Live trapping is vital for monitoring small mammal population, yet trap type can affect capture success across habitats, species, and sexes. Here we compared metal Sherman traps and wooden Dziekanówka traps in paired setup across forest, meadow, and wetland habitats in the Lower Oder Valley, recording 878 captures. Wooden trap yielded 67% of captures, with forest- dwelling Apodemus flavicollis and meadow-dwelling A. agrarius showing habitat-specific preferences for wooden traps. Male shrews ( Sorex spp.) were more frequently captured in wooden traps, indicating sex-related behavioural differences. No trap preference was observed in Clethrionomys glareolus and Microtini species. These results suggest that wooden traps provide better microclimatic conditions and reduced disturbance, enhancing capture rates for certain taxa and sexes. Combining trap types is recommended to minimize sampling biases and improve population assessments, particularly for insectivorous small mammals in heterogeneous habitats.

Large scale monitoring of terrestrial small mammals using noninvasive sampling and COI barcoding - Clara Stefen; Thalia Jentke; Tobias Birkwald; Jana Chmieleski; Jan Decher; Andrea Kaus-Thiel; Carsten Morkel; Jonas Thielen; Ronny Goldberg; Jens Jakobitz; Henrietta Atzig; Anke Müller; et al. (Mammal Research, 2025)
Terrestrial small mammals are important elements of the food chain, and like other species affected by climate change. Knowledge about their current distribution is of interest to model future developments and monitoring biodiversity loss. However, their monitoring is challenging due to legal restrictions. Here we document a pilot study testing the performance of a non-invasive monitoring strategy for terrestrial small mammals. It uses baited tubes in the field to collect fecal pellets combined with molecular species identification using COI barcodes. Just over 1000 samples were collected mainly in 2021 in 2506 trap nights, nine areas and 36 specific sites across Germany in habitats located close to waterbodies. COI-PCR products were obtained from 93% of samples and 55% of samples could be assigned to a small mammal species based on high-quality Sanger-Sequences. We found 11 species of Eulipotyphla and Rodentia while local communities were dominated by Apodemus sp. and Clethrionomys glareolus . We showed that the described strategy enables large-scale biomonitoring of small terrestrial mammals as it combines three advantages: 1) welfare of the animals is not affected and therefore time-consuming paperwork to obtain legal permits like for live-trapping is not required, 2) field work can be done by volunteers and 3) molecular species identification can be implemented in the routine work of molecular laboratories. Future tests with tube diameters, bait, timing of placement etc. could increase the “capture” success and demonstrate the applicability of the method to rare species. Also, some training for the involved field workers could be advantageous.

Forest refugia and riverine barriers promote diversification in the W est A frican pygmy shrew ( C rocidura obscurior complex, S oricomorpha) - François Jacquet; Violaine Nicolas; Marc Colyn; Blaise Kadjo; Rainer Hutterer; Jan Decher; Bertin Akpatou; Corinne Cruaud; Christiane Denys (Zoologica Scripta, 2014)
The Crocidura obscurior or West African pygmy shrew complex is endemic to West African forests from south‐eastern Guinea, eastern Liberia, southern Côte d'Ivoire and south‐western Ghana. We explore the genetic and morphometric diversity of 239 individuals of the C. obscurior complex from 17 localities across its geographical range. Using genetic data from three mitochondrial (16S, cytochrome b and COI ) and four nuclear markers ( BRCA 1, STAT 5A, HDAC 2 and RIOK 3) and skull geometric morphometrics, we show that this complex is composed of two cryptic and sympatric species, C. obscurior and C. eburnea . We then test several hypotheses to infer their evolutionary history. The observed phylogeographical pattern based on cytochrome b and COI sequences fits the forest refuge theory: during arid phases of the Plio‐Pleistocene, around 3.5, 2.1, 1 and 0.5 Mya, a small number of populations survived in isolated forest patches and diverged allopatrically. During wetter climatic periods, forests expanded, leading to secondary contacts between previously isolated populations. Our results also suggest the possible contribution of episodes of isolation in subrefuges. Historical variation of the West African hydrographic network could also have contributed to the observed patterns of genetic differentiation. Rivers such as the Volta and Sassandra may act as past and/or current barriers to gene flow. Although these two species have sympatric distributions, their phylogeographical histories are somewhat dissimilar due to small differences in their dispersal abilities and ecological requirements.

Conservation, Small Mammals, and the Future of Sacred Groves in West Africa - Jan Decher (Biodiversity and Conservation, 1997)